Delta-Aminolevulinic Acid-Mediated Photodiagnoses in Surgical Oncology: A Historical Review of Clinical Trials - Georges, Joseph F.; Valeri, Amber; Wang, Huan; Brooking, Aaron; Kakareka, Michael; Cho, Steve S.; Al-Atrache, Zein; Bamimore, Michael; Osman, Hany; Ifrach, Joseph; Yu, Si; Li, Carrie; et al. (Frontiers in Surgery, 2019)
Fluorescence imaging is an emerging clinical technique for real-time intraoperative visualization of tumors and their boundaries. Though multiple fluorescent contrast agents are available in the basic sciences, few fluorescence agents are available for clinical use. Of the clinical fluorophores, delta aminolevulinic acid (5ALA) is unique for generating visible wavelength tumor-specific fluorescence. In 2017, 5ALA was FDA-approved for glioma surgery in the United States. However, clinical studies suggest this agent may have utility in surgical subspecialties outside of neurosurgery. Data from dermatology, OB/GYN, urology, cardiothoracic surgery and gastrointestinal surgery show 5ALA is helpful for intraoperative visualization of malignant tissues in multiple organ systems. This review summarizes data from English-language 5ALA clinical trials across surgical subspecialties. Imaging systems, routes of administration, dosing, efficacy and related side effects are reviewed. We found that modified surgical microscopes and endoscopes are the preferred imaging devices. Systemic dosing across surgical specialties range between 5-30mg/kg bodyweight. Multiple studies discussed potential for skin irritation with sun exposure, however this side effect is infrequently reported. Overall, 5ALA has shown high sensitivity for labeling malignant tissues and providing a means to visualize malignant tissue not apparent with standard operative light sources.